Percepção de discriminação cotidiana entre estudantes do curso de medicina de uma universidade pública do Estado de Minas Gerais - Marcos Ferreira Benedito (2020)
Discrimination as a structuring element of Brazilian social dynamics, brings out unequal and excluding social relations. Discrimination can be defined as unfair behavior or treatment motivated by a person's belonging to a particular social group considered inferior or different from the dominant group. The objective of the present work is to verify the perception of daily discrimination among medical students at a public university in the State of Minas Gerais. A cross-sectional study was carried out with 1470 medical students in 2018. Sociodemographic data, related to the course, and some behaviors were analyzed. To identify the perception of discrimination, the Daily Discrimination Scale was used. The results show that 50.5% of the participants are female; 55.6% aged up to 22 years; 62.2% white, 79.7% heterosexual. A percentage of 18.8% of students realized that people think they are better than them, 11.5% that they were treated less gently, 9.5% that people treat you as if you were not smart, and 8.6 % with less respect, all very frequently. The perception of discrimination present was associated with non-white skin color (56.3% vs. 43.9% among whites); being in the LGBT group (59.2% vs. 45.8% among heterosexuals); being a beneficiary of financial aid (57.9% vs. 46.0% among non-beneficiaries); and being in the basic cycle of the course (54.3%) (p <0.001). The main reasons cited for the occurrence of these events were gender, physical appearance, age, education and income, sexual orientation and skin color. The importance of studies with in-depth studies on the impacts of discrimination on students' health and the identification of strategies to enable an academic environment more sensitive to everyday discrimination is indicated.